A Review on Formation and Decay Kinetics of Trihalomethanes in Water of Different Qualities. Issue 12 (25th April 2014) - Al‐Omari, Abbas; Muhammetoglu, Ayse; Karadirek, Ethem; Jiries, Anwar; Batarseh, Mufeed; Topkaya, Bulent; Soyupak, Selcuk
<x xml:space="preserve">Abstract</x> Despite the many disadvantages associated with the use of chlorine for disinfecting drinking water, chlorination is still the main method used for this purpose worldwide. Low chlorine concentrations in water distribution systems increase health risks whereas high chlorine concentrations are associated with the formation of disinfection by‐products such as trihalomethanes which are suspected carcinogens. Due to their negative health impacts, trihalomethanes occurrence in finished drinking water has received great attention from researchers and scientists worldwide. This manuscript critically reviews and discusses up to date knowledge on the occurrence of trihalomethanes in chlorinated drinking water and their associated health risks and identifies research gaps. The models for trihalomethane formation and decay have been compiled with special emphasis on the impact of the bromide ion on the total trihalomethane levels and speciation. Furthermore, the fate and transport of trihalomethanes in drinking water supplies and in groundwater have been investigated. Finally, management options for the reduction of trihalomethanes in chlorinated drinking water such as the removal of precursors from raw water, the use of alternative disinfectants and the removal of trihalomethanes from finished drinking water have been critically investigated and discussed.